Návrh standardizácie ranného odberu mocu pre stanovenie hladín NTx u pacientov s osteoporózou - Wendlová, J (Vnitrni lekarstvi, 2001)
UNLABELLED: The authors examined 79 patients (n = 79) with primary and secondary osteoporosis, incl.31 men (nM = 31) aged 31-61 years and 48 women (nF = 48, aged 33 to 65 years. In these patients they assessed NTx (amino-terminal telopeptide of type I collagen of the Ist organic bone matrix) in 24 (NTx24) and 2-hour morning (NTx2) diuresis (from 6 to 8 a.m.). OBJECTIVE: 1. To assess the relationship between values of NTx in th suggested 2-hour diuresis and NTx values in the standard 24- hour diuresis differentiated by sex. 2. To compare the ratio (index) of widths of 95% confidence intervals (CI) for NTx2 and NTx24 with the ratio (index) of reference widths (manual OSTEX, USA) for NTx in the first morning urine (NTx1) and for NTX24 differentiated by sex. 3. Evaluate the suggested 2-hour diuresis for assessment of NTx. STATISTICAL ANALYSIS: Stochastic-determinist linear regression analysis. RESULTS: 1. Between values NTx24 and NTx2 a statistically significant regression correlation was found (p < 0.001) (men: r = 0.352, women r2 = 0.781). The indices of widths of reference limits (IR) of OSTEX Co. USA reach values 2.1 times higher (0.7 times) than indices of widths of CI for osteoporosis (IO) in men as well as women. CONCLUSION: 1. Between values of NTx24 and NTx2 is a significant regression relation. Both urine samples can be used for assessment of the NTx level. 2. Higher values of IR and IO indices for women as well as men confirm a greater dispersal of NTx1 values as compared with NTx2 values. 3. Introduction of two-hour morning diuresis will reduce the extent of variation of NTx values during repeated examinations and provide more accurate information as compared with assessment of NTx in any of the first morning samples of urine according to instructions of the manufacturers of the kits.
Keywords: Humans; lidé středního věku; kolagen typu I; osteoporóza; Diuresis; Female; Aged; dospělí; Collagen Type I; senioři; lidé; Biomarkers; kolagen; Collagen; peptidy; Peptides; Adult; biologické markery; ženské pohlaví; Male; Middle Aged; Specimen Handling; diuréza; Osteoporosis; odběr biologického vzorku; mužské pohlaví